2012
DOI: 10.3189/2012jog10j238
|View full text |Cite
|
Sign up to set email alerts
|

Melt regimes, stratigraphy, flow dynamics and glaciochemistry of three glaciers in the Alaska Range

Abstract: We used ground-penetrating radar (GPR), GPS and glaciochemistry to evaluate melt regimes and ice depths, important variables for mass-balance and ice-volume studies, of Upper Yentna Glacier, Upper Kahiltna Glacier and the Mount Hunter ice divide, Alaska. We show the wet, percolation and dry snow zones located below ~2700ma.s.l., at ~2700 to 3900ma.s.l. and above 3900ma.s.l., respectively. We successfully imaged glacier ice depths upwards of 480 m using 40-100 MHz GPR frequencies. This depth is nearly double pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Diffusion of chemistry within snow and firn caused by melt, and an associated lack of stratigraphy or more diffuse horizons imaged in radar profiles are well-documented phenomena (e.g. Campbell and others, 2012).
Fig.
…”
Section: Resultsmentioning
confidence: 94%
“…Diffusion of chemistry within snow and firn caused by melt, and an associated lack of stratigraphy or more diffuse horizons imaged in radar profiles are well-documented phenomena (e.g. Campbell and others, 2012).
Fig.
…”
Section: Resultsmentioning
confidence: 94%
“…Perhaps the best illustration of the effects of melt on stratigraphy is the snowpack stable isotope profile. Although isotope stratigraphy is altered within the upper snow layers, at least compared with profiles from higher sites (Campbell et al ., ), below the ash layer, the record of variability nearly disappears. Oerlemans () and Takeuchi and Li () have demonstrated that a decrease in the albedo (in this case from volcanic ash) will lead to intensified melting.…”
Section: Discussionmentioning
confidence: 99%
“…and cold mean annual temperature (−17 °C), the Mt. Hunter drill site has flat‐lying and conformable subsurface stratigraphy in ice‐penetrating radar profiles indicating that the record is not disturbed by complex glacier flow (S. Campbell et al, ). After processing at the National Ice Core Laboratory in Denver, CO, the ice cores were transported frozen to Dartmouth College and sampled using a continuous ice core melter system (see Breton et al, ; Osterberg et al, , for melter system details and detection limits).…”
Section: Methodsmentioning
confidence: 99%